As diretrizes de formação de professores no Brasil: análise da implementação da BNC-Formação em cursos de Pedagogia em universidades de Sorocaba/SP - Dias, Amanda Regina Martins (2024)
This research aimed to analyze the implementation of the Common National Base for Initial Teacher Training for Basic Education (BNC-Formação) in Pedagogy courses at two universities located in Sorocaba/SP, one public and the other private, verifying their alignment with the new guidelines, according to the requirements of CNE/CP Resolution No. 2/2019, from 2019 to 2023. The chosen approach was qualitative, exploratory and documentary. The study used a review of specialized literature, documentary analysis of the Pedagogical Projects of the Pedagogy Courses (PPCs) of the universities analyzed, in addition to the application of semi-structured questionnaires to two coordinators and six teacher trainers, in order to obtain their perceptions about the process of implementing the guidelines. Data analysis was carried out based on Bardin's (2009) content analysis methodology. The results of the research revealed that, although efforts to adapt Pedagogy courses to the new BNC-Formação guidelines were made, significant divergences were found between the perceptions of coordinators and teacher trainers regarding the implementation of the guidelines. Among these divergences, the most notable are curricular standardization, seen as a limitation to teacher autonomy, and the lack of adequate training for the application of the new competencies and skills provided for by the BNCC. As advances, the research identified an increased emphasis on pedagogical practice and greater alignment with the demands of basic education. The initial thesis of this research, which pointed to insufficient dialogue in the formulation of Resolution No. 2/2019 by the representative teaching segments, making consonance impossible in the period proposed for its implementation, was confirmed by the results found. The analysis of the data revealed that the communication process between higher education institutions and basic education did not materialize effectively, resulting in inconsistencies in the implementation of the BNC-Formação guidelines. Both coordinators and teacher trainers pointed out difficulties in adapting to the new requirements, highlighting the lack of a deeper and more collaborative dialogue between universities and regulatory bodies. The research emphasizes the need for a more effective dialogue between training institutions and regulatory bodies, suggesting that teacher training should balance the integration of the skills provided for by the BNC-Formação with the appreciation of the pedagogical and critical autonomy of future educators.